Using Virtual Reality to Compare Design Alternatives Using Subjective and Objective Evaluation Methods. (January 2020) - Wingler, Deborah; Joseph, Anjali; Bayramzadeh, Sara; Robb, Andrew
Objective: This study sought to develop a method that supports a more evidence-based approach to evaluating multiple design options in virtual reality (VR), combining subjective insights gathered using traditional approaches and objective feedback gathered using the VR platform. Additionally, this study sought to understand how objective data garnered from the VR platform could be used to compliment traditional evaluation strategies. Background: VR can be a viable research platform for supporting evidence-based design practices. Prior studies have predominately utilized experiential user feedback. While able to provide valuable subjective insights, these approaches are less effective in making objective comparisons between multiple designs alternatives. Method: A repeated measures study was conducted with nursing faculty. User feedback was captured through surveys, interviews, and the VR platform. Results: The survey, interview, and the objective VR data converged in terms of identifying the highest performing design option. Survey data showed that Room 2 performed best in terms of perceived physical access to supplies, unobstructed movement, and availability of space to accommodate additional equipment. VR data showed that participants in Room 2 had significantly higher visibility to both patient and care partners throughout their simulated interaction. Conclusion: Simulation-based evaluations in VR that use a combination of users' subjective insights and objective data obtained from VR can be an effective tool for helping designers evaluate multiple design options. The use of scenario-based simulations provided a structured and clinically relevant approach to comparing three preoperative rooms, supporting a more robust assessment of users' physical response to a simulated healthcare environment.